Is executive control related to working memory capacity and fluid intelligence? - Rey-Mermet, Alodie; Gade, Miriam; Souza, Alessandra S; von Bastian, Claudia C; Oberauer, Klaus (Journal of experimental psychology. General, 2019)
In the last two decades, individual-differences research has put forward 3 cognitive psychometric constructs: executive control (i.e., the ability to monitor and control ongoing thoughts and actions), working memory capacity (WMC, i.e., the ability to retain access to a limited amount of information in the service of complex tasks), and fluid intelligence (gF, i.e., the ability to reason with novel information). These constructs have been proposed to be closely related, but previous research failed to substantiate a strong correlation between executive control and the other two constructs. This might arise from the difficulty in establishing executive control as a latent variable and from differences in the way the 3 constructs are measured (i.e., executive control is typically measured through reaction times, whereas WMC and gF are measured through accuracy). The purpose of the present study was to overcome these difficulties by measuring executive control through accuracy. Despite good reliabilities of all measures, structural equation modeling identified no coherent factor of executive control. Furthermore, WMC and gF-modeled as distinct but correlated factors-were unrelated to the individual measures of executive control. Hence, measuring executive control through accuracy did not overcome the difficulties of establishing executive control as a latent variable. These findings call into question the existence of executive control as a psychometric construct and the assumption that WMC and gF are closely related to the ability to control ongoing thoughts and actions. (PsycINFO Database Record (c) 2019 APA, all rights reserved).